Abrogation of mercuric chloride-induced nephritis in the Brown Norway rat by treatment with antibodies against TNFα - A. Molina; F. Sánchez-Madrid; T. Bricio; A. Martín; E. Escudero; V. Alvarez; F. Mampaso (Mediators of Inflammation)
HgCl2 induces an autoimmune disease in the Brown Norway rat characterized by synthesis of autoantibodies (mainly, anti-GBM Abs), severe proteinuria and interstitial nephritis. Also, HgCl2- injected rats develop glomerular cell infiltrates consisting of ED1+ cells (monocyte/macrophage), starting on day 4 and reaching a maximum on day 8. Treatment with anti-TNF-α antiserum had preventative effects as it reduced the urinary protein levels to close to the normal range and also blocked the influx of inflammatory cells in the renal glomeruli and interstitium, but circulating anti-GBM and lineal glomerular IgG deposits were unmodified. In addition, whole isolated glomeruli from HgCl2-induced nephritis secreted TNF-α commencing on day 8, being maximally detected on day 11 and preceding, between 2 to 3 days, the development of proteinuria. The administration of anti-TNF-α antiserum or anti-α4 integrin mAb completely abrogated the synthesis of TNF-α in glomeruli isolated from the respective treated groups of animals, in addition to the proteinuria. Taken together our results confirm that TNF-α plays an important role in the induction and development of HgCl2-induced nephritis and highlights the pathogenic importance of the local release of TNF in those renal diseases in which prominent glomerular macrophage accumulation is a constant feature.